PERAN WORLD TRADE ORGANIZATION (WTO) DALAM PENYELESAIAN SENGKETA PERDAGANGAN LARANGAN IMPOR PRODUK PERIKANAN JEPANG OLEH KOREA SELATAN - Suryani "; Yusnarida Eka Nizmi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research is a studies of international relation which has purpose for analyzing the role of the world trade organization that well known as World Trade Organization (WTO) to solve the world trade problem. In 2011, there was a natural disasters and earthquake for the magnitude 9 tremor in Japan. This disaster coused a nuclear power plant leak owned by Tokyo Electronic Power Co. (TEPCO) in the Fukushima area. South Korea has forbidden fall out of Japanese fishery products.The method in this research is qualitative research. The data comes from books, journals, theses, documents, articles, internet sites and other sources related to research. Perspective of Neoliberalism Institutionalism by Robert Keohane and the theory of the International Trade Regime were used to analyze for the level of system.The result of this study are efforts and procedures which proposed by Japan so that South Korea prohibition on import to perform the test toward their fishery products. The settlement took place under the supervision of the Dispute Agency (DSB). The WTO dispute panel said that South Korea's actions were initially justified, but made their position violate the WTO Sanitary and Phytosanitary (SPS) agreement. South Korea submitted an appeal and the result was that the Appeals Agency failed to consider whether the contamination testing method proposed by Japan would fully meet South Korea's protection standards. The Appeals Agency overturned the decision by the lower panel on the four points disputed namely discrimination, trade restrictions, transparency and the inspection process put forward by Japan.  Keywords: Settlement of Japan - South Korea, World Trade Organization (WTO), Sanitary and Phytosanitary Agreements, Dispute Settlement Body .